Konflik Peran dan Pengalaman Audit dalam Mempengaruhi Audit Judgment dengan Skeptisisme Profesional Sebagai Variabel Mediasi - Surbakti, Manuel Aristo; Wijayanti, Nanda Ayu (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p01, 2022)
This study aims to analyze the effect of role conflict and audit experience on audit judgment and skepticism of the professionalism of public accountants as mediating variables. This research is an explanatory research with a quantitative approach. Data was collected using a questionnaire to 47 KAPs in the city of Surabaya. Sampling was done by purposive sampling, then analyzed using path analysis and Sobel test. The results of the study explain that role conflict has a negative effect, while audit experience has a positive effect on audit judgment. On the indirect effect, it is known that role conflict also has a negative effect and experience has a positive effect on audit judgment through professional skepticism from public accountants in Surabaya. Keywords: Role Conflict; Audit Experience; Professional Skepticism; Audit Judgment.